Serum Magnesium concentration in normal and preeclamptic pregnancy: A tertiary center experience - Tuli, Jesmin Zahan; Biswas, Prithwy Shankar; Hussain, Muhammad Shakhawat; Hasan, Md Mehedi; Mondal, Tithi (Mediscope, 2024)
Preeclampsia and maternal mortality are more prevalent in underdeveloped nations. Preeclampsia has an estimated 16% incidence rate in Bangladesh, which is extremely high. One of the body's major macronutrients is magnesium. It also serves a multitude of enzymes as a cofactor. This cross-sectional study was done in the department of Biochemistry of Mymensingh Medical College, Mymensingh, from July 2016 to June 2017. This study involved a total of 100 individuals, where 50 preeclamptic patients and 50 healthy pregnant women served as the case and control groups, respectively. The results were shown as mean ±SD. For both the case and control groups, the mean ±SD of serum magnesium levels were 1.75 ±0.22 mg/dl and 1.63 ±0.21, respectively. Comparison of the mean ±SD of serum magnesium in the case and control groups revealed a highly significant difference (P<0.001). Students' unpaired ‘t’ test was used to compute the statistical difference. Mediscope 2024;11(2): 73-76